IMPLEMENTASI TEKNOLOGI MBG UNTUK OPTIMALISASI AERASI PADA KOLAM BUDIDAYA LELE DI KANUTAN, BANTUL - Astyanto, Achilleus Hermawan; Winarbawa, Heryoga; Roshanti, Fatma; Dyaksa, Gilang Argya; Seen, Michael; Kusbandono, Wibowo; Rines, Rines; Purwadianto, Doddy; Sugiharto, Budi; Setyahandana, Budi; Mustain, Fahra Diky; Jaladri, Stefano (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2025)
In the present work, a simple aeration technology, utilizing the concept of a microbubble generator (MBG), was applied to an aquaculture field. It aims to support aeration by increasing the dissolved oxygen (DO) in the water. Subsequent supporting activities were carried out, comprising design, optimization and manufacturing, installation, and trials of MBG units, followed by site exposures. During one of the exposures, two sessions covering a discussion and another practical work were conducted. The working principle of the MBG was briefly explained in the first session, while the installation and operation were practically elaborated in the second session. Additionally, two units of MBG appliances were granted to be applied on the exposure site, namely Usaha Budidaya Ikan Senandung Betta. During the following exposure, the MBG implementation was evaluated through a series of DO measurements. Here, the measurement reached a range of 5.7 – 5.9 mg/L by operating the MBG. This means that the MBG increases the DO by around 1.5 mg/L.